2018
DOI: 10.1002/oby.22291
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Composition with Blood Pressure and Hypertension

Abstract: Objective The present study investigated the associations of body composition, including skeletal muscle and fat mass, with blood pressure (BP) and hypertension. Methods Data from 3,130 participants aged 18 to 80 years were analyzed. Body composition and total skeletal muscle (TSM) were measured or calculated based on dual‐energy x‐ray absorptiometry. Multivariate linear and logistic regression models were used to analyze the associations of TSM, body fat percentage, android to gynoid fat ratio, and leg and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
10
24
0
Order By: Relevance
“…The paths mainly consisted of a sequence of changes in leg score, blood glucose, and g-GTP among the intervention variables. The direction of change in these variables was consistent with conventional clinical knowledge for improving blood pressure [29][30][31][32][33][34][35] . For example, high-blood glucose levels have been reported to be a risk factor of hypertension.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The paths mainly consisted of a sequence of changes in leg score, blood glucose, and g-GTP among the intervention variables. The direction of change in these variables was consistent with conventional clinical knowledge for improving blood pressure [29][30][31][32][33][34][35] . For example, high-blood glucose levels have been reported to be a risk factor of hypertension.…”
Section: Discussionsupporting
confidence: 73%
“…Important features comprised items related to hypertension, such as age, body composition (leg score, body mass index (BMI), and waist), blood glucose, and gamma glutamyl transferase (g-GTP) [27][28][29][30][31][32][33][34][35] . Therefore, the selected explanatory variables were considered to be reasonable for SBP predictive models from the clinical perspective.…”
Section: Application On Actual Health Checkup Datasetmentioning
confidence: 99%
“…Overweight is a well-recognized risk factor for pre-hypertension and hypertension and studies have suggested that the risk of developing hypertension may be linked to body fatness and body fat distribution (Wiklund et al, 2008; Ye et al, 2018). Similarly, excess adiposity is characterized by elevated sympathetic nervous system activity, even in young healthy individuals, which is likely to impact on their CV risk including hypertension development (Lambert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 The unfavorable relationship between LBM and hypertension has been found in cross‐sectional studies, while opposite findings were also reported. 7 , 8 , 9 , 10 Such inconsistency was probably resulted from the variances of populations, as well as the utilities of different measurements of LBM. On the other hand, the deficiency of longitudinal design in published studies made it failed to verify the causality between increased LBM and hypertension.…”
Section: Introductionmentioning
confidence: 99%